1987
DOI: 10.1002/jnr.490180125
|View full text |Cite
|
Sign up to set email alerts
|

Central action of interleukin‐1 in altering the release of tsh, growth hormone, and prolactin in the male rat

Abstract: In order to determine the possible effects of interleukin-1 on the release of pituitary hormones by direct action on the brain, the peptide was injected into the third brain ventricle of conscious, unrestrained male rats and the effects on hormone release were compared with effects on rectal temperature. The procedure of blood sampling and intraventricular injection resulted in a significant decline in body temperature and a decrease in plasma growth hormone without alteration in the plasma level of thyroid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(43 citation statements)
references
References 7 publications
2
40
0
1
Order By: Relevance
“…However, another study showed that i.c.v. administration of IL-1 stimulated GH secretion (Rettori et al 1987). In contrast, a continuous i.v.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, another study showed that i.c.v. administration of IL-1 stimulated GH secretion (Rettori et al 1987). In contrast, a continuous i.v.…”
Section: Discussionmentioning
confidence: 90%
“…However, the effect of cytokines on GH secretion is not well known. IL-1 administration has been reported both to increase (Rettori et al 1987) and decrease (Peisen et al 1995) GH secretion. Similarly, tumor necrosis factor-(TNF ) has also been reported to increase (Rettori et al 1989, Elsasser et al 1991 and decrease (Walton & Cronin 1989) GH secretion.…”
Section: Introductionmentioning
confidence: 99%
“…LPS is a potent stimulus of GH secretion [5] and also of IL-1. In vivo, IL-1 causes the release of GH [34]. These findings suggest that the process of infection or inflammation and consequent immune activation can affect neuroendocrine function.…”
Section: Discussionmentioning
confidence: 90%
“…At this time, t h e v o l u m e s o f c o r p o r a l u t e a a n d p l a s m a progesterone levels were significantly increased. Furthermore, Rettori et al [19] reported the release of prolactin, which stimulates corpora lutea, by IL-1 administration into the brain ventricles of rats. There is a possibility that the endometritis might induce release of prolactin via some cytokines.…”
Section: Discussionmentioning
confidence: 99%